MiR-30a-5p Overexpression May Overcome EGFR-Inhibitor Resistance through Regulating PI3K/AKT Signaling Pathway in Non-small Cell Lung Cancer Cell Lines - Meng, Fei; Wang, Fengfeng; Wang, Lili; Wong, S. C. Cesar; Cho, William C. S.; Chan, Lawrence W. C. (Frontiers in Genetics, 2016)
Lung cancer is one of the most common deadly diseases worldwide, most of which is non-small cell lung cancer (NSCLC). The epidermal growth factor receptor (EGFR) mutant NSCLCs frequently respond to the EGFR tyrosine kinase inhibitors (EGFR-TKIs) treatment, such as Gefitinib and Erlotinib, but the development of acquired resistance limits the utility. Multiple resistance mechanisms have been explored, e.g. the activation of alternative tyrosine kinase receptors (TKRs) sharing similar downstream pathways to EGFR. MicroRNAs (MiRNAs) are short, endogenous and non-coding RNA molecules, regulating the target gene expression. In this study, we explored the potential of miR-30a-5p in targeting the EGFR and insulin-like growth factor receptor-1 (IGF-1R) signalling pathways to overcome the drug resistance. IGF-1R is one of the tyrosine kinase receptors that share the same EGFR downstream molecules, including phosphatidylinositol 3 kinase (PI3K) and protein kinase B (AKT). In this work, an in vitro study was designed using EGFR inhibitor (Gefitinib), IGF-1R inhibitor (NVP-AEW541), and miRNA mimics in two Gefitinib-resistant NSCLC cell lines, H460 and H1975. We found that the combination of EGFR and IGF-1R inhibitors significantly decreased the phosphorylated AKT (p-AKT) expression levels compared to the control group in these two cell lines. Knockdown of phosphoinositide-3-kinase regulatory subunit 2 (PIK3R2) had the same effect with the dual inhibition of EGFR and IGF-1R to reduce the expression of p-AKT in the signalling pathway. Overexpression of miR-30a-5p significantly reduced the expression of the PI3K regulatory subunit (PIK3R2) to further induce cell apoptosis, and inhibit cell invasion and migration properties. Hence, miR-30a-5p may play vital roles in overcoming the acquired resistance to EGFR-TKIs, and provide useful information for establishing novel cancer treatment.